The European board of orthodontists: a challenge at any stage. (2nd April 2019) - Brierley, Catherine; Hodge, Trevor
Abstract : Recognizing differences in the standards of orthodontic postgraduate education across Europe, the European Board of Orthodontists was established in 1997 with the aim of providing a standard against which an orthodontist could be judged independent of national barriers and, in so doing, promoting high standards of care. This article describes the experiences of both authors who sat the assessment at the June 2018 diet held at the European Orthodontic Congress in Edinburgh. CPD/Clinical Relevance: Application for membership to the European Board of Orthodontists requires clinicians to work towards illustrating well-described and applied clinical procedures to correct significant orthodontic problems to an identified excellent standard. In the pursuit of attaining this recognition, orthodontists will invariably reflect on the treatments they provided and undoubtedly learn more, as well as seeing improvements in the standard of their patients' care.